An Empirical Investigation of Libyan Professional Accounting Services - EL-SHARIF, YOUNIS (Dirasat in Economics and Business, 1980)
The growth of the Libyan economy during the second half of this century has placed burdens upon the public accounting profession in Libya. Investors, creditors, and managers as well as state agencies need much more reliable information in order to make their daily decisions in relation to the economic development of the country. Therefore, the Libyan public accounting firms are expected to provide many reliable accounting services. Examples of these services are auditing, bookkeeping, services concerning liquidations, tax services, and systems design and installations. Much has been written about these services in the environment of developed nations such as the United States and other western countries. However, few studies have been done to evaluate empirically the extent to which these services are provided in a developing nation such as Libya. Therefore, the purpose of this study is to evaluate and analyze empirically the current conditions of the professional accounting services in Libya. The study's major hypothesis is as follows: Many professional accounting services are not widely provided by the public accounting profession in Libya because of the characteristics of the Libyan accounting firms, the size of their clients and the shortage of qualified accountants.